Sweeping practices, perceptions and knowledge about occupational safety and health hazards of street sweepers in Dhaka city, Bangladesh: a qualitative inquiry - Kabir, Ashraful; Farhana, Nadia; Akter, Farzana; Jesmin, Shahana; Ali, Ahsan (International Journal Of Community Medicine And Public Health, 2017)
Background: Street sweepers play important roles for keeping the cities clean. Their works entail removing of debris from streets, collecting solid waste, disposing and recycling waste material. Consequently, they have higher chances to be exposed to numerous risk factors; therefore, their occupational safety and health hazard became crucial. There is little evidence about the sweeping practices, perceptions and knowledge on their occupational safety and health hazards. The objective of the study is to explore current sweeping practices, perceived risk and the level of knowledge of a group of street sweepers of Dhaka city. Methods: An explorative qualitative research design was used. We conducted 15 IDIs, 8 KIIs and 5 FGDs with Telegu street sweepers, community and religious leaders and NGO workers in two different sweeper colonies in Dhaka City. Results: Due to the manual handling process, the street sweepers are often exposed to a variety of risks factors – exhaust fumes, extreme noise, toxic substances and dust particles. Frequent infections and injuries were reported commonly as they lack basic safety equipment’s during works. Low perceived health hazards were prevalent. Strong faith-based explanations were found to rationalize possible health hazards. Conclusions: A number of socio-economic factors influence the level of knowledge and risk perception. Interventions on awareness building program coupled with behaviour change counselling (BCC) activities would be appropriate to address the lack of knowledge on health hazards and low risks perception.